Travel motivations of first-time, repeat, and serial backpackers. (October 2019) - Møller Jensen, Jan; Hjalager, Anne-Mette
This study explores travel motivations of first-time, repeat, and serial backpackers. Data were obtained through an online survey administered to a convenience sample of Danish backpackers. Using explorative factor analysis on 40 motivational variables drawn from the research literature, the study delineated eight push and five pull motivational factors. Among them, Stimulation, Host-site Involvement, and Nature are the three most important motivational factors. Sun and Beach, Gastronomic Experiences, Recognition, and Volunteering are the least rated motivational factors. Additionally, the study detects differences in motivational factors between first-time, repeat, and serial backpacker trips. While first-time and repeat backpackers only differ on self-actualization and gaining recognition, factors which are rated higher among first-time backpackers; serial backpackers rate eight of the thirteen motivational factors lower than first-time backpackers. Thus, the results support a quest for a more detailed classification of backpackers, instead of the traditional first-time versus repeat backpacker distinction. Implications for academics and practitioners as well as suggestions for further research are provided at the end of the article.